Vertebral osteomyelitis following transrectal ultrasound-guided - Rajgopal, Raghav; Wang, Yuding; Faber, Kenneth J.; Izawa, Jonathan I. (Canadian Urological Association Journal, 2013)
Transrectal ultrasound-guided needle biopsy of the prostate (TRUS) is a well-tolerated and standardized procedure for the diagnosis of prostate cancer. Complications associated with TRUS requiring emergency room visits or hospital admissions are relatively low and include complications, such as a 1% risk of urinary retention and less than 1% chance of bacterial sepsis. Vertebral osteomyelitis is a rare complication of TRUS; there are 3 reported cases. Vertebral osteomyelitis has an insidious onset and usually resolves following medical intervention. We present an extremely rare case of vertebral osteomyelitis following TRUS, its clinical outcome and management.